Performance evaluation of starfive visionfive v2 and comparison on intel up board and raspberry pi 4b - Loh, Le Zhou (2024)
RISC-V is an open instruction set architecture that defines the set of instructions that a machine can understand. Since it is an open ISA, RISC-V is free to implement without having to pay royalties. VisionFive 2 is a RISC-V single board computer with an integrated GPU that has improved processor work frequency and multimedia processing capabilities compared to its previous version, VisionFive 1. VisionFive has been one of the competitors of Raspberry Pi [1]. Over the span of years, users have been comparing different coprocessors to understand the relative performance of these devices. This can help them understand which coprocessor is the best for a specific workload. By comparison and performance benchmark users can also find potential improvements to the device. PTS benchmarking also known as Phoronix Test Suite benchmarking is an open-source benchmarking software that is widely used to assess performance of Linux systems [2]. This thesis aims to perform PTS benchmarking to measure and evaluate performance of Starfive Visionfive 2, Starfive Visionfive 1 and Raspberry Pi 4B.